Dampak Afasia terhadap Kemampuan Komunikasi Anak di Lingkungan Pendidikan - Anggraini, Elya Siska; Lubis, Siti Khodijah; Wardani, Dwie Nola; Nisa, Khoirun; Julafni, Mia; Nasution, Nayla Amanda (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Aphasia is a language disorder that can impair an individual's ability to speak, understand, read, and write. In children, aphasia poses a significant developmental challenge, particularly in educational settings. This disorder affects the child's ability to communicate effectively with teachers and peers, directly impacting both learning outcomes and social interactions. This article explores the impact of aphasia on children's communication abilities within educational environments and emphasizes the importance of adaptive communication strategies and inclusive teaching approaches. Using a qualitative approach and literature review, this study examines the roles of teachers, families, and professionals in supporting children with aphasia. Findings highlight that early intervention, emotional support, and the use of alternative communication methods can significantly improve participation and learning outcomes for children with aphasia. Collaboration between schools and speech-language therapists is essential to create an educational environment that is both supportive and responsive to the needs of children with language impairments.